Contact activation of C3 enables tethering between activated platelets and polymorphonuclear leukocytes via CD11b/CD18 - Hamad, Osama A.; Mitroulis, Ioannis; Fromell, Karin; Kozarcanin, Huda; Chavakis, Triantafyllos; Ricklin, Daniel; Lambris, John D.; Ekdahl, Kristina N.; Nilsson, Bo (Thrombosis and Haemostasis, 2015)
Complement component C3 has a potential role in thrombotic pathologies. It is transformed, without proteolytic cleavage, into C3(H2O) upon binding to the surface of activated platelets. We hypothesise that C3(H2O) bound to activated platelets and to platelet-derived microparticles (PMPs) contributes to platelet-PMN complex (PPC) formation and to the binding of PMPs to PMNs. PAR-1 activation of platelets in human whole blood from normal individuals induced the formation of CD16+/CD42a+ PPC. The complement inhibitor compstatin and a C5a receptor antagonist inhibited PPC formation by 50 %, while monoclonal antibodies to C3(H2O) or anti-CD11b inhibited PPC formation by 75–100 %. Using plasma protein-depleted blood and blood from a C3-deficient patient, we corroborated the dependence on C3, obtaining similar results after reconstitution with purified C3. By analogy with platelets, PMPs isolated from human serum were found to expose C3(H2O) and bind to PMNs. This interaction was also blocked by the anti-C3(H2O) and anti-CD11b monoclonal antibodies, indicating that C3(H2O) and CD11b are involved in tethering PMPs to PMNs. We confirmed the direct interaction between C3(H2O) and CD11b by quartz crystal microbalance analysis using purified native C3 and recombinant CD11b/CD18 and by flow cytometry using PMP and recombinant CD11b. Transfectants expressing CD11b/CD18 were also shown to specifically adhere to surface-bound C3(H2O). We have identified contact-activated C3(H2O) as a novel ligand for CD11b/CD18 that mediates PPC formation and the binding of PMPs to PMNs. Given the various roles of C3 in thrombotic reactions, this finding is likely to have important pathophysiological implications.
Keywords: Complement C3; platelets; microparticles; PMN; platelet-leukocyte complex